Slovanské literatury v evropském kontextu: zvláštnosti vývoje a promýšlení alternativ - Stehlík, Petr; Pospíšil, Ivo; Šaur, Josef; Dohnal, Josef; Černý, Marcel; Pilch, Pavel (Masaryk University Press, 2024)
Title in English: Slavic literatures in the European context: the specifics of development and reflections on alternatives The dynamics of the development and character of Slavic literature show numerous specific features which mostly result from their asynchronous nature and intermittent continuity, but also from the creative ways of adopting external influences, which affected the work of writers from Slavic countries within the world literary process. The authors of the present edited volume aim to explore some of the peculiarities of Slavic literature in the context of European literary development and at the same time to point out selected cases of reflecting the alternatives formulated by their representatives in relation to the prevailing domestic discourse of the time, as well as to the European models.